The Emergence of the Incel Community as a Misogyny-Motivated Terrorist Threat - Lockyer, Demeter (Terrorism and political violence, 2025)
The incel (involuntary celibate) community is characterized by misogynistic beliefs surrounding women and a fatalistic outlook on society. Incels have committed, or have attempted to commit, several acts of mass violence globally, which suggests they are an emerging terror threat. In this study, we discuss how incels position their violence as ideological terrorism, how this violence is tied to misogyny despite incels’ additional targeting of non-women, and finally, the extent to which incels are, or at least claim to be, anti-violence or otherwise non-violent. To do this, we inductively analysed over 1000 comments from a popular incel forum, Incels.is, detailing how incels discuss three mass-murderers associated with the incel community: Elliot Rodger, Alek Minassian, and Jake Davison. Through revealing the ways incels discuss these three men, we conclude that incels view their own violence as terrorism with ideological aims, thus qualifying the community as a terrorist threat.